The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1177/0308518x17752681
|View full text |Cite
|
Sign up to set email alerts
|

How market standards affect building design: The case of low energy design in commercial offices

Abstract: This paper develops existing work on building design through a focus on one important yet understudied form of regulation: market standards. Market standards are agreed upon definitions of 'necessary' provision in buildings and are fundamental in 'formatting' markets and determining the value of a building in the market. The paper presents a case study of the design of 10 commercial offices in London, UK, the effects of market standards on the designs and on the potential for the development of lower energy bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…In summary, in this sample almost all aspects of speculative office design were strongly standardized through conformity to these sets of regulations, guidelines and norms, which can be called 'market standards' (Faulconbridge et al, 2017). These have cumulative consequences in that they interlock and are backed by three forms of institutional legitimacy (Scott, 2008), with regulative standards demanding legal 'de minima', frequently backing up normative expectations of, for example, the environmental performance implied but not guaranteed by EPCs and BREEAM, and the cognitive-cultural demands of 'quality' represented by particular aesthetics, but more concretely BCO compliance and exceedance.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…In summary, in this sample almost all aspects of speculative office design were strongly standardized through conformity to these sets of regulations, guidelines and norms, which can be called 'market standards' (Faulconbridge et al, 2017). These have cumulative consequences in that they interlock and are backed by three forms of institutional legitimacy (Scott, 2008), with regulative standards demanding legal 'de minima', frequently backing up normative expectations of, for example, the environmental performance implied but not guaranteed by EPCs and BREEAM, and the cognitive-cultural demands of 'quality' represented by particular aesthetics, but more concretely BCO compliance and exceedance.…”
Section: Discussionmentioning
confidence: 96%
“…Such features as location and quality materials are undeniably linked with high-value buildings, but their influence is not the focus of this paper, which discusses buildings' expected or modelled energy efficiency. It is in this area that the most detail regarding what have been treated elsewhere (Faulconbridge et al, 2017) as different institutionally legitimated 'market standards' could be found.…”
Section: Agent Demands Not Occupier Preferences (Ii)mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the increase in green neighbourhood numbers has been facilitated and accompanied by a significant increase in the number of inter/national green building or neighbourhood standards and certification systems that seek to guide and regulate urban development such as LEED 1 in North America and BREEAM 2 in Europe. These schemes can be described as offthe-shelf, easy-to-transfer models 3 that are often incorporated into local (municipal) regulations thereby prescribing certain standards for new developments (Faulconbridge et al, 2018 (Bulkeley and Castán Broto, 2013).…”
Section: The Local-global Making Of Urban Sustainability and Green Nementioning
confidence: 99%